Managing risk in a failing IT project: A social constructionist view - LIM, Wee-Kiat (Institutional Knowledge at Singapore Management University, 2011)
Why do IT projects continue to stumble, despite the proliferation of risk management methodologies and a growing body of knowledge on project risk assessment and mitigation? In this paper, we propose an alternative theoretical perspective that views project risk as a social construction process shaped by the risk accounts of social groups and actors within an implementation context. Risk management is embedded in the social processes where risks are negotiated and contested, with some risk accounts amplified and some attenuated. Through the analysis of a large IT implementation in an Asian logistics firm and its trajectory of successive crises, we examine the process of the social construction of risk. Our findings highlight the inherent fragmentation and the challenge of building collectiveness in risk construction, and the need for risk managers to consider the influence of broader social structures and the reshaping dynamism of sudden focusing events in managing complex IT projects.